2002
DOI: 10.1152/japplphysiol.00755.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of albuterol enantiomers on ciliary beat frequency in ovine tracheal epithelial cells

Abstract: Frohock, Jeffrey I., Corrine Wijkstrom-Frei, and Matthias Salathe. Effects of albuterol enantiomers on ciliary beat frequency in ovine tracheal epithelial cells. J Appl Physiol 92: 2396-2402, 2002. First published February 8, 2002 10.1152/japplphysiol.00755.2001.-␤ 2-Adrenergic agonists stimulate ciliary beat frequency (CBF), an integral part of mucociliary clearance. To evaluate the differential effects of albuterol enantiomers and their racemic mixture on ciliary function, CBF and intracellular calcium were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
(35 reference statements)
2
23
0
1
Order By: Relevance
“…Stimulation of cAMP-dependent PKA seems to play an important role as the next step in the β-AR signaling pathway to stimulate CBF. Many β-adrenergic agonists such as isoproterenol, [24][25][26][27] SBM, 22,28) TBl, 11,13) fenoterol, 29) and salmeterol 30,31) have been used in previous studies, but SBM and TBL were used in the present study to confirm the validity of our in vitro evaluation system. It has been reported that R-SBM and racemic SBM increased CBF by 24 and 13%, respectively, in a dose-dependent manner (10 µm to 1 mm).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Stimulation of cAMP-dependent PKA seems to play an important role as the next step in the β-AR signaling pathway to stimulate CBF. Many β-adrenergic agonists such as isoproterenol, [24][25][26][27] SBM, 22,28) TBl, 11,13) fenoterol, 29) and salmeterol 30,31) have been used in previous studies, but SBM and TBL were used in the present study to confirm the validity of our in vitro evaluation system. It has been reported that R-SBM and racemic SBM increased CBF by 24 and 13%, respectively, in a dose-dependent manner (10 µm to 1 mm).…”
Section: Discussionmentioning
confidence: 60%
“…20) Many investigators have extensively studied the regulation of CBF using ciliated epithelial cells and have clarified that β-adrenergic agonists stimulate the CBF of ciliated epithelial cells. 21) β-Adrenergic agonists have been shown to have various effects on epithelial cells, such as the stimulation of CBF 21,22) and chloride secretion toward the airway lumen, 23) which could contribute to the enhanced mucociliary function by β-adrenergic agonists. It has been reported that β-AR activation in ciliated cells increased CBF through the fol- lowing two mechanisms: a calcium-coupled mechanism and calcium-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…After expansion, passage-2 NHBE cells were seeded on plastic 6-or 12-well culture plates at a density of 1.0 ϫ 10 4 cells/cm 2 . Medium (modified bronchial epithelial cell basal medium) was changed every other day until cultures were 80-90% confluent, at which time the cells were incubated in medium, from which bovine pituitary extract and human recombinant epidermal growth factor were removed for 24 h to force cells into a quiescent, nonproliferative state.…”
Section: Primary Culture Of Nhbe Cellsmentioning
confidence: 99%
“…Agonists of G␣ s -coupled receptors and forskolin that increase intracellular cAMP through stimulation of transmembrane adenylyl cyclases (tmACs) all stimulate CBF, and these effects can be blocked with inhibitors of cAMP-dependent protein kinase A (PKA) (Di Benedetto et al, 1991;Frohock et al, 2002;Lansley et al, 1992;Sanderson and Dirksen, 1989;Tamaoki et al, 1989b;Verdugo et al, 1980;Wyatt et al, 1998;Yang et al, 1996). In analogy to the situation in Paramecium (Hamasaki et al, 1991;Hamasaki et al, 1989), cAMP possibly regulates CBF by activating PKA localized to the axoneme by its A kinase anchoring protein (Kultgen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%